Parallel transmission for ultrahigh‐field imaging. (19th May 2015) - Padormo, Francesco; Beqiri, Arian; Hajnal, Joseph V.; Malik, Shaihan J.
Abstract : The development of MRI systems operating at or above 7 T has provided researchers with a new window into the human body, yielding improved imaging speed, resolution and signal‐to‐noise ratio. In order to fully realise the potential of ultrahigh‐field MRI, a range of technical hurdles must be overcome. The non‐uniformity of the transmit field is one of such issues, as it leads to non‐uniform images with spatially varying contrast. Parallel transmission (i.e. the use of multiple independent transmission channels) provides previously unavailable degrees of freedom that allow full spatial and temporal control of the radiofrequency (RF) fields. This review discusses the many ways in which these degrees of freedom can be used, ranging from making more uniform transmit fields to the design of subject‐tailored RF pulses for both uniform excitation and spatial selection, and also the control of the specific absorption rate. © 2015 The Authors. NMR in Biomedicine published by John Wiley & Sons Ltd. Abstract : Ultrahigh‐field MRI provides a powerful new investigational device for in vivo imaging, but is hindered by non‐uniform and variable radiofrequency fields. Parallel transmission (PTx) promises to address these issues by providing more control over the fields. In this article, we review methods for exploiting the new degrees of freedom provided by PTx to improve image quality and to reduce the specific absorption rate (SAR).